QUR'ANIC AND PSYCHOLOGICAL FOUNDATIONS OF SELF-ESTEEM;: Toward an Integrative Framework for Adolescent Suicide Prevention - Asep Muksin; Ahmad Thib Raya; Nur Arfiyah Febriani; Arafat Mohamed Ahmed Othman (STAIN Majene, 2026)
The phenomenon of increasing suicide rates among adolescents is a serious issue that requires attention from various parties. One of the psychological factors that influence suicidal tendencies is low self-esteem. This article aims to examine the concept of self-esteem from the perspective of the Qur'an and psychology and explore its contribution as a preventive approach to suicide among adolescents. This study uses a thematic interpretation (maudhû'i) method of Qur'anic verses related to self-respect, human dignity, and spiritual awareness, and analyzes them using modern psychological theories. The results of the study show that the Qur'an emphasizes human dignity and the importance of building positive self-awareness, while psychology explains that self-esteem is formed from individual experiences and the environment. The integration of the two shows that strengthening self-esteem through spiritual education and psychological guidance can be an effective strategy in preventing adolescent suicidal behavior. These findings emphasize the importance of a holistic approach in fostering adolescent mental health.